Emerging Fatal Ib/CC12 Hypervirulent Multiresistant Streptococcus agalactiae in Young Infants With Bloodstream Infection in China - Liu, Jingxian; Chen, Feng; Guan, Hongyan; Yu, Jiajia; Yu, Jing; Zhao, Jing; Liu, Ying; Shen, Lisong (Frontiers in Microbiology, 2021)
Streptococcus agalactiae (also known as group B Streptococcus [GBS]) is a tremendous threat to young infants. Eighty pediatric GBS infection cases were enrolled from a teaching hospital in Shanghai between 2009 and 2020; among them, 72.5% (58/80) were diagnosed with bloodstream infection (BSI). Sequence types (STs) and serotypes of associated GBS strains were identified, and most of the Ⅰb/clonal complex (CC)12 (86.7%, 13/15) strains caused BSIs, which was significantly higher than that of the genetically related clone Ⅰb/CC10 (20%, 2/10) (P < 0.05). Ⅰb/CC12 BSI (30.8%) mortality was significantly higher than that of non-Ⅰb/CC12 BSI (2.2%) (P < 0.05). Virulence genes associated with adhesion, invasion, and immune evasion were detected using polymerase chain reaction. The fbsA and gbsPC1 positive rates of Ⅰb/CC12 strains was higher than that of non-Ⅰb/CC12 strains, whereas cpsIaJ, cpsJ, cpsI, and cpsG positive rates were lower than those of non-Ib/CC12 (P < 0.05). In in vitro studies, the Ⅰb/CC12 strains had strong invasiveness in RAW264.7 cells, but less invasiveness in human umbilical vein endothelial cells, human brain microvascular endothelial cells, and human mammary epithelial cells when compared to other two clones. In the in vivo model, the Ⅰb/CC12 GBS invaded the circulation system more rapidly after intraperitoneal injection, was more difficult to eradicate by phagocytes, and caused significantly higher mortality than Ⅰb/CC10 and Ⅲ/ST17 (P < 0.05). Genome analysis showed that the Ⅰb/CC12 strains had two clustered regularly interspaced short palindromic repeat-Cas systems and carried more antibiotic resistant genes, which conferred resistance to macrolides, clindamycin, aminoglycosides, and tetracycline. The Ⅰb/CC12 strains had 45 unique annotated genes compared to that of Ⅰb/CC10, including the pathogen-related toxin/antitoxin system, PezA/T. In conclusion, Ⅰb/CC12 is an emerging hypervirulent multiresistant GBS clone that causes invasive and fatal infections in pediatric patients. The prevention and control of Ⅰb/CC12 GBS infection should be emphasized.